The Ijtihād of Prophet; Analytical Comparison between Sunni and Shiah - Nur, Sultan (Universitas Islam Negeri Alauddin Makassar, 2021)
This article aims to reveal the nature of Ijtihad in the eyes of linguists and scholars of Usul Fiqh from the Sunni and Shia circles. After that, it goes to the core of the discussion, which is trying to explain what the Ahlusunnah's views regarding Ijtihad on the Prophet are, of course, accompanied by the arguments and arguments—then followed by an explanation of how the Shia perspective on the issue of the Prophet's Ijtihad. The study results show that Ijtihad on the Prophet saw is a classic issue that has been a long discussion, and each has a different view and is supported by accurate and conclusive arguments. Those who support the view that the Prophet SAW in issuing laws for an issue have used the Ra'yu and Ijtihad (Qiyas) methods, and this view is in great demand by the Ahlussunnah scholars. Of course, this view is not without solid arguments. It is even supported by arguments from the Qur'an and hadith, which are the primary basis and source for every problem. The second group argues that it is impossible for the Prophet to Ijtihad in using Qiyas and Ra'yu because everything is clear enough for the Prophet and no longer requires any effort to use Ijtihad to uncover the law of a problem. Supporters of this view are mainly formed from among scholars or scholars of Usul Fiqh of the Imamiyah Shia School.